Negotiating norms in nature: The moral landscape of outdoor recreation and nature based tourism in North Troms - Svensson, Gaute (UiT Norges arktiske universitet, 2016)
Paper 3 and 4 of this thesis are not available in Munin. Paper 3: Svensson, G., Viken, A.; “Respect in the girdnu: the Sami verdde institution and tourism in North Norway.” (Manuscript) Paper 4: Svensson, G.: Do you have any particular favorite place: Hunters‘ and anglers‘ secrets meet tourism in North Norway”. (Manuscript) This dissertation is about norms of the outdoors and it is based in four publications. While the articles are about specific norms, the summary article focus on how these norms are negotiated between locals and tourists and how they in sum can be seen as a negotiable room – a moral landscape of the outdoors. Firstly, I set out to investigate how nature based tourism is affecting the normative negotiations among hunters, anglers and outdoor recreationists in North Troms. Secondly, I have focused on what these norms can do. The data presented in this dissertation are collected through participant observation and interviews. The fieldwork was conducted over 12 months between 2011 and 2012. The fieldwork includes participatory engagements with tourists, guides, companies and locals outside the industry. This comprises activities like ice fishing, small game hunting, canoe paddling, salmon angling, glacier hikes and deep sea angling. The most extensive part of the fieldwork was a four months internship with a nature based tourism company in the region. During the internship I got to work as a co-guide as well participate as customer to test their products. The main finding of this dissertation is that nature based tourism has a substantial impact on how outdoor recreation is practiced and how acceptable behavior in nature is negotiated and reconstructed in North Troms. The norm denotes the line between the acceptable and the un-acceptable. The negotiations about where this line should be drawn mark the processes that altogether constitute morality. These processes are characterized by a tension and overlap between outdoor recreation and tourism as something non-commercial and commercial, that I ...